Comparison of simulation models in terms of quantity and allocation of land change. (July 2015) - Camacho Olmedo, María Teresa; Pontius, Robert Gilmore; Paegelow, Martin; Mas, Jean-François
Abstract: Our article illustrates how to compare the outputs from models that simulate transitions among categories through time. We illustrate the concepts by comparing two land change models: Land Change Modeler and Cellular Automata Markov. We show how the modeling options influence the quantity and allocation of simulated transitions, and how to compare output maps from pairs of model runs with respect to a reference map of transitions during the validation interval. We recommend that the first step is to assess the quantity of each transition and to determine the cause of the variation in quantity among model runs. The second step is to assess the allocation of transitions and to determine the cause of the variation in allocation among model runs. The separation of quantity and allocation of the transitions is a helpful approach to communicate how models work and to describe pattern validation. Highlights: We compare three runs of models that simulate transitions among land categories. Pattern validation compares a reference map of transition to maps from pairs of runs. Quantity and allocation are helpful concepts to describe models and to compare maps. Quantity refers to the size of each transition from one category to another category. Allocation refers to the spatial distribution of the transitions.